2012
DOI: 10.5888/pcd9.120065
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Poor Glycemic Control or Wide Glycemic Variability Among Diabetes Patients in Hawaii, 2006–2009

Abstract: IntroductionAlthough glycemic control is known to reduce complications associated with diabetes, it is an elusive goal for many patients with diabetes. The objective of this study was to identify factors associated with sustained poor glycemic control, some glycemic variability, and wide glycemic variability among diabetes patients over 3 years.MethodsThis retrospective study was conducted among 2,970 diabetes patients with poor glycemic control (hemoglobin A1c [HbA1c] >9%) who were enrolled in a health plan i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
85
7
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(117 citation statements)
references
References 28 publications
17
85
7
8
Order By: Relevance
“…In accordance with our result, Assunção et al and Juarez et al also found significant association between longer duration of diabetes and poor glycemic control [30, 31]. This association may be due to the decreases in β -cell function and insulin secretion as the disease progresses over time.…”
Section: Discussionsupporting
confidence: 92%
“…In accordance with our result, Assunção et al and Juarez et al also found significant association between longer duration of diabetes and poor glycemic control [30, 31]. This association may be due to the decreases in β -cell function and insulin secretion as the disease progresses over time.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, 36.5% of participants achieved good glycemic control. The present study is consistent with a study reported from Mekelle, Tigray [9], Jimma [10], Addis Ababa [11], and Hawaii [12]. The present finding is higher than a study reported from jimma [13].…”
Section: Discussioncontrasting
confidence: 39%
“…Although stress is highly personalized and its perception can vary depending on personality type, interpretation of life events and cultural context [58], the nature of some occupations may be more stressful than others. Similarly, length of time since DM onset has been directly related to glycemic control [59] so we recognize the need to have included these two variables but they were not available. Secondly, participants were enrollees of the HMO and results may not be generalizable to uninsured patients, those in other health insurance system or patients in other geographic locations.…”
Section: Discussionmentioning
confidence: 98%